Modulation of Cholesterol Pathways in Human Macrophages Infected by Clinical Isolates of Leishmania infantum - Manzano, José Ignacio; Perea-Martínez, Ana; García-Hernández, Raquel; Andrés-León, Eduardo; Terrón-Camero, Laura C.; Poveda, José Antonio; Gamarro, Francisco (Frontiers in Cellular and Infection Microbiology, 2022)
To increase our understanding of factors contributing to therapeutic failure (TF) in leishmaniasis, we have studied some plasma membrane features of host THP-1 cells infected with clinical isolates of Leishmania infantum from patients with leishmaniasis and TF. The fluorescent probes DPH and TMA-DPH were used to measure changes in membrane fluidity at various depths of the plasma membranes. Steady-state fluorescence anisotropy of DPH embedded in the infected THP-1 membranes showed a significant increase, thereby suggesting a substantial decrease in plasma membrane fluidity relative to controls. Considering that cholesterol affects membrane fluidity and permeability, we determined the cholesterol content in plasma membrane fractions of human macrophages infected with these L. infantum lines and observed a significant increase in cholesterol content that correlates with the measured decrease in plasma membrane fluidity. In order to define the pathways that could explain the increase in cholesterol content, we studied the transcriptomics of the cholesterol-enriched pathways in host THP-1 cells infected with TF clinical isolates by RNA-seq. Specifically, we focused on four enriched Gene Ontology (GO) terms namely cholesterol efflux, cholesterol transport, cholesterol metabolic process and cholesterol storage. Additionally, we analyzed the genes involved in these pathways. Overall, this study shows that these clinical isolates are able to modulate the expression of specific genes in host cells, thereby modifying the cholesterol content in plasma membranes and inducing changes in plasma membrane fluidity that could be associated with the parasite’s ability to survive in the host macrophages, thereby possibly contributing to immune evasion and TF.